Handbook on the economics and theory of the firm - Dietrich, Michael; Krafft, Jackie (Cheltenham, 2012)
"This unique Handbook explores both the economics of the firm and the theory of the firm, two areas which are traditionally treated separately in the literature. On the one hand, the former refers to the structure, organization and boundaries of the firm, while the latter is devoted to the analysis of behaviours and strategies in particular market contexts. The novel concept underpinning this authoritative volume is that these two areas closely interact, and that a framework must be articulated in order to illustrate how linkages can be created."